Socio-demographic factors influencing to glaucoma related blindness among patients attending eye clinic at Kenneth Matiba Eye and Dental Hospital, Murang'a County, Kenya - Ndung’u, Violet Wanjiru; Maritim, Violet; Kariuki, John (International Journal Of Community Medicine And Public Health, 2025)
Background: Glaucoma, a leading cause of blindness, affects 76 million people worldwide, projected to reach 111.8 million by 2040. It causes 15% of global blindness, with 600,000 people losing sight annually. Risk factors include age, gender, education, income, and family history. In Kenya, glaucoma affects 4.3% of the population, accounting for 23% of blindness, with low surgical feasibility despite increasing healthcare access. Methods: This study used an analytical cross-sectional design, combining quantitative (interviewer-administered questionnaires) and qualitative (Key Informant Interviews) methods to collect data from 187 glaucoma patients at Kenneth Matiba Eye and Dental Hospital between July and September 2024. Ethical approval was obtained, and systematic random sampling was used. Quantitative data were analyzed with SPSS v29, while qualitative data were analyzed thematically. Reliability testing showed a Cronbach Alpha of 0.810. Statistical significance was set at p<0.05. Results: At least 120 (64.2%) of respondents had visual impairment related to glaucoma of which 46 (38.3%), 34 (28.3%) and 17 (14.2%) had moderate impairment, mild impairment and complete blindness. Age between 30-39 years (OR: 7.958, p=0.032), unemployment (p=0.027), and lack of health insurance (OR: 5.525, p=0.014), income levels of <Ksh 10,000 (OR: 12.708, p=0.028), and family history of glaucoma (OR: 5.919, p=0.012) were factors associated with glaucoma blindness. Conclusions: The study highlighted the link between visual impairment and social determinants, showing healthcare disparities tied to income, insurance, geography, and family history. It emphasizes the need for a multifaceted approach to prevention and treatment.